Adapting to change, perceptions and knowledges in the involvement of Aboriginal peoples in forest management : a case study with Lac Seul First Nation - Larose, Desneiges (2009)
This study examines the involvement of Aboriginal peoples in forest management and their perceptions and understandings of the forest, forest management, participation, consultation and Aboriginal and Treaty rights in Ontario's Treaty Three area. Seeking to inform knowledge-sharing in forest management from the perspective of the Anishinaabe of Treaty Three, notions of knowledge, ways of knowing, epistemological underpinnings, as well as recommendations and the shared experiences of participants, are examined.